PERSELISIHAN PARTAI POLITIK DI GORONTALO - Salahudin Pakaya (Maleo Law Journal, 2017)
This study aims to determine the forms of internal party strife and analyze the legal aspects of the event such dispute. This research is located in the province of Gorontalo period 2005 - 2008, using normative and empirical research methods, which discussion is a descriptive-qualitative. The data collected in this study was obtained by means of depth interviews with a number of people who understand the object of a study and supported by documents issued by the competent institutions associated with political parties' internal disputes in Gorontalo Province. The results showed that the dispute form political parties in Gorontalo, are: 1) disputes with regard to the board; 2) violation of the rights of party members; and 3) Westernised against the party's decision. While it can be put forward four (4) related to the legal aspects of the dispute a political party, namely: 1) political party disputes can be resolved through the courts; 2) the settlement of disputes through mediation, arbitration is a settlement out of court; 3) decisions of political parties should be based on AD / ART party, because the party's decision-making in accordance AD / ART is guaranteed by UU No. 2 Tahun 2008 on Political Parties; and 4) political party disputes could result in the loss of the right and authority officials and party members.Keywords : Dispute, Political Parties